2014
DOI: 10.1007/s40122-014-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Assisted Dying: Acceptance by Physicians Only for Patients Close to Death

Abstract: This study reports on German physicians’ views on legalization of euthanasia and physician-assisted suicide, comparing this with a similar survey of UK doctors. A questionnaire was handed out to attendants of a palliative care and a pain symposium. Complete answers were obtained from 137 physicians. Similar to the UK study, about 30% of the physicians surveyed support euthanasia in case of terminal illness and more support physician-assisted suicide. In contrast, in both countries, a great majority of physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
0
3
0
2
Order By: Relevance
“…This particular group of professionals is also of special interest in the debate since some have declared euthanasia and PAS as possible outcomes of palliative care [ 22 – 24 ]. In the year before a study was performed at the same conference [ 25 , 26 ]. However, that study focused on support of the legalization of euthanasia or PAS rather than exploring whether the respondents would actually be willing to perform the act.…”
Section: Introductionmentioning
confidence: 99%
“…This particular group of professionals is also of special interest in the debate since some have declared euthanasia and PAS as possible outcomes of palliative care [ 22 – 24 ]. In the year before a study was performed at the same conference [ 25 , 26 ]. However, that study focused on support of the legalization of euthanasia or PAS rather than exploring whether the respondents would actually be willing to perform the act.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a negative relationship between completed training in palliative care and a positive approach to executing an ES (Marini et al., 2006 ; Zenz et al., 2014 ). However, a recent report analyzing physicians’ practices in caring for patients with ALS showed no influence of training in palliative care on PAS but noted a more liberal attitude toward continuous sedation until death and withdrawal of IV (Thurn et al., 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…Attendants were physicians and nurses. It is the third in a series of surveys on attitudes concerning end-of-life care among professionals interested in the field of palliative care [ 7 9 ].…”
Section: Methodsmentioning
confidence: 99%